Property and Constitution - AJ van der Walt (Pretoria University Law Press (PULP), 2012)
Property and Constitution by AJ van der Walt 2012 ISBN: 978-1-920538-12-5 Pages: vi 212 Print version: Available Electronic version: Free PDF available